Optimization of impeller blade number in centrifugal pump for crude oil using Solidworks Flow Simulation - Aldio, Muhammad Fikhri; Waskito, Waskito; Purwantono, Purwantono; Lapisa, Remon (Researcher and Lecturer Society, 2023)
Every type of fluid to be transferred has specific characteristics such as viscosity, density, friction, and others, thus requiring the selection of the appropriate pump type. One of the factors influencing the performance of a centrifugal pump is the number of blades used. This research aims to explore the influence of the number of blades on a centrifugal pump used as a fluid transfer device for crude oil. The study was conducted using the Computational Fluid Dynamics (CFD) method. The analyzed variations of the number of blades included three options, namely centrifugal pumps with 12, 14, and 16 blades. Based on the simulation results conducted using Solidworks Research License 2021-2022 software, it was found that the centrifugal pump with 12 blades exhibited the most optimal performance. The simulation results show uniform flow and pressure around the mid-span plane of the 12-blade impeller. In the case of the 12-blade impeller, the flow thrown by the centrifugal force is concentrated in the middle of the channel towards the outlet, resulting in higher pressure and volume flow rates.